Mastering PHP design patterns : develop robust and reusable code using a multitude of design patterns for PHP 7 - Ali, Junade (Packt Publishing, 2016)
Develop robust and reusable code using a multitude of design patterns for PHP 7 About This Book Learn about advanced design patterns in PHP 7 Understand enhanced architectural patterns Learn to implement reusable design patterns to address common recurring problems Who This Book Is For This book is for PHP developers who wish to have better organization structure over their code through learning common methodologies to solve architectural problems against a backdrop of learning new functionality in PHP 7. What You Will Learn Recognize recurring problems in your code with Anti-Patterns Uncover object creation mechanisms using Creational Patterns Use Structural design patterns to easily access your code Address common issues encountered when linking objects using the splObserver classes in PHP 7 Achieve a common style of coding with Architectural Patterns Write reusable code for common MVC frameworks such as Zend, Laravel, and Symfony Get to know the best practices associated with design patterns when used with PHP 7 In Detail Design patterns are a clever way to solve common architectural issues that arise during software development. With an increase in demand for enhanced programming techniques and the versatile nature of PHP, a deep understanding of PHP design patterns is critical to achieve efficiency while coding. This comprehensive guide will show you how to achieve better organization structure over your code through learning common methodologies to solve architectural problems. You'll also learn about the new functionalities that PHP 7 has to offer. Starting with a brief introduction to design patterns, you quickly dive deep into the three main architectural patterns: Creational, Behavioral, and Structural popularly known as the Gang of Four patterns. Over the course of the book, you will get a deep understanding of object creation mechanisms, advanced techniques that address issues concerned with linking objects together, and improved methods to access your code. You will also learn about Anti-Patterns and the best methodologies to adopt when building a PHP 7 application. With a concluding chapter on best practices, this book is a complete guide that will equip you to utilize design patterns in PHP 7 to achieve maximum productivity, ensuring an enhanced software development experience. Style and approach The book covers advanced design patterns in detail in PHP 7 with the help of rich code-based examples.